The - Illies, Christian (Clarendon,Oxford University Press, 2003)
Is it merely a matter of taste or convention to consider something right or wrong? Or can we find good reasons for our values and judgements that are independent of culture and tradition? The problem is as old as philosophy itself; and after more than two millennia of scholarly debate, there seems no end to the controversy. But Christian Illies suggests that powerful new forms of transcendental argument (a philosophical tool known since antiquity) may offer a long-sought cornerstone for morality